ANALISIS KASUS BULLYING PADA ANAK - Wiwid Widyastuti; Edy Soesanto (Adisam Publisher, 2023)
Bullying is the act of using power to hurt a person or group of people verbally, physically or psychologically so that the victim feels depressed, traumatized and helpless, which is carried out repeatedly and carried out by one group on one particular individual. Bullying is carried out purely for fun, generally in the form of insults, hate speech, and even physical violence, both mild and severe. In Indonesia, the problem of bullying is still quite serious, because every year bullying cases continue to increase. Therefore, it is necessary to overcome cases of bullying that are currently occurring. The impact felt by the victim due to bullying that occurs on the victim can usually have mental, emotional and physical impacts. The worst impact resulting from bullying can result in severe depression experienced by the victim. Bullying can be triggered by several factors, namely personality, family and the environment, both school and social. This research was carried out with the aim of conducting a literature review regarding the understanding of bullying, the impact of bullying, the factors that cause bullying, and the environment of a bully. This type of research uses a qualitative approach with a literature review method. Based on the research results, analysis of cases of bullying in children uses a qualitative descriptive analysis method. Identifying cases of bullying problems that occur in children will make it easier to pinpoint a bullying problem.